C17 Increased mitochondrial number, cellular stress and glycogen accumulation in heart of minipig model transgenic for N-terminal part of human mutated huntingtin. (13th September 2016) - Rodinova, Marie; Ondruskova, Nina; Dosoudilova, Zaneta; Juhas, Stefan; Juhasova, Jana; Ellederova, Zdenka; Motlik, Jan; Hansikova, Hana
Abstract : Background: Minipig model transgenic for N-terminal part of human mutated huntingtin (TgHD) created in Libechov allows us to study the development of Huntington's disease (HD) in the long-term context. Aim: To monitor mitochondrial structure and metabolism in high energy demand tissues from TgHD and WT minipigs. Material and methods: Ultrastructure was analysed by transmission electron microscopy, oxidative phosphorylation system (OXPHOS) complexes activity and content were measured by spectrophotometric and immunoelectrophoretic methods in heart, muscle and brain of 36 and 48 month (M) old animals. Furthermore, polarographic measurement of respiration and analysis of capacity of mitochondrial energy generation system (MEGS) were performed in muscle. Results: Increased number of mitochondria, increased fibrosis, glycogen accumulation and slightly decreased levels of selected OXPHOS subunits were detected in 48 M old TgHD heart. Decreased respiration and altered capacity of MEGS and levels of OXPHOS complexes I, III and IV were observed in muscle. Slight alterations of ultrastructure in basal ganglia and altered activities of OXPHOS complexes in frontal cortex were detected in 48 M old TgHD brain. Conclusion: Our results contribute to understanding of physiological consequences of the earliest changes – preclinical signs in different tissues manifest in HD. Supported by Czech-Norwegian Financial Mechanism 2009–2014 and MSMT under project "HUNTINGTON" 7F14308, COST LD15099 (MSMT) and NPU LO1609 (MSMT)